Efficient CFO Compensation Method in Uplink OFDMA for Mobile WiMax - Lakshmanan Muthukaruppan; Parthasharathi Mallick; Nithyanandan Lakshmanan; Sai Krishna Marepalli (LPPM ITB, 2016)
Mobile WiMax uses Orthogonal Frequency Division Multiple Access (OFDMA) in uplink where synchronization is a complex task as each user presents a different carrier frequency offset (CFO). In the Data Aided Phase Incremental Technique (DA-PIT) estimation is performed after FFT operation to use the received frequency domain pilot subcarrier information. As estimation is done in the presence of noise, there exists some offset error, which is called residual frequency offset (RFO). The Simple Time Domain Multi User Interference Cancellation scheme (SI-MUIC) is a time domain approach which takes a longer time delay to compensate the CFO effect for the last user. Decorrelation-Successive Interference Cancellation (DC-SC) and Integrated Estimation and Compensation (IEC) are frequency domain approaches that compensate the CFO effect with a more complex method for ICI cancellation. The Modified Integrated Estimation and Compensation technique (Modified IEC) is proposed for better residual CFO compensation. The proposed technique has better performance due to its efficient suppression of ICI and MUI. The difference between the CFOs of two OFDMA symbols lies within the range of RFO that is not considered in the conventional compensation techniques, such as the SI-MUIC, DC-SC and IEC compensation techniques.